Epistemological and methodological foundations of adult education research – a personal statement - Schmidt-Hertha, Bernhard (Adult Education Discourses, 2025)
This text outlines the author’s personal epistemological and methodological foundations in adult education research, emphasizing a journey of continuous learning and openness. It is written on the basis of 25 years of research experience and many empirical projects. One main thesis is that a curious and open approach to research paradigms is crucial, alongside lifelong learning research. Further, maintaining clear epistemological and philosophical positions is essential to avoid arbitrariness. Here a constructivist view is adopted, acknowledging that the social world is interpreted and meaning-laden, interpretations are shaped by shared patterns (culture, language) and individual experiences. However, social structures and inequalities, while socially constructed, impact individual actions. Social phenomena in this sense are both objectively structured and subjectively interpreted. Thus, research must address the interplay of individual agency and social structures. A pragmatistic methodology, advocating for flexible method selection based on the research question, is put at the forefront. Pragmatism acknowledges the context-dependent nature of research and the influence of researchers’ beliefs. Aiming for use-inspired basic research, generalizable knowledge derived from real-life problems should be addressed. Research can inform pedagogical practice by offering new perspectives and challenging traditional interpretations. At the same time, one has to be aware that research findings are subject to diverse interpretations, requiring clear and honest communication. Regarding the concrete realization of research projects, the article argues for selecting methods carefully and considering a range of factors. Ethical considerations are paramount, and the pros and cons of mixed-method designs are discussed. Certain preconditions that are relevant for all research projects are examined here, namely openness, teamwork and collaborative exchange, continuous dialogue, networking, and time.